Random Interaction Effect of Digital Transformation on General Price Level and Economic Growth - Byung Gwun Choy (Foresight and STI Governance)
The paper attempts to evaluate the impact of digital transformation upon productivity using the multi-level structure model of a random interaction effect based on the Bayesian approach to cross-section data. Digital transformation significantly raised general price levels in Russia and has had consistently significant positive effects upon economic growth through the random interaction effect. Therefore, in Russia in 2018, digital transformation played a role as a driver of technological progress that prompted economic growth rather than economic stability.